Legal Nature of the Will of Spouses under the Legislation of Ukraine - DYAKOVYCH, Myroslava (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018, 2018)
The article represents peculiarities of legal regulations of the will of spouses under the legislation of Ukraine. The author has made a comparative and legal analysis of the institute of joint will of spouses under the legislation of foreign countries, in particular, Germany, USA. As a result of judicial practice analysis, typical mistakes, which occur in the judicial practice, notarial practice in the realization of the joint will of spouses, are pointed out. In the conclusion, the need for legal editing of article 1243 of the Civil Code of Ukraine is substantiated.